UPAYA MENINGKATAN MINAT BELAJAR BAHASA INDONESIA MELALUI MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND. LEARNING (CTL) PADA SISWA KELAS VIII.1 SMP NEGERI 2 LUBUK PAKAM - Dermauli Sitorus; Rita Manulung (Center for Research and Community Service (LPPM) University of Abulyatama, 2021)
The success of educational goals is mainly determined by the teaching and learning process experienced by students. Students who learn will experience changes in knowledge, understanding, reasoning, skills, values, and attitudes. In order for these changes to be achieved properly, various factors are needed to produce the desired changes, namely the effective understanding of the concept. In the Bahasa Indonesian lesson, the students’ interest in student learning was still low. Many students can not understand properly and correctly. In evaluating many of the students' scores below the KKM.. This classroom action research aimed: 1) To find out the application of the Contextual Teaching and Learning (CTL) Model in increasing the Learning Interest; 2) To know the increasing of the students’ interest in learning through the application of the CTL Model; 3) How is the students’ responses toward the material for understanding the text of moral stories/fables through the application of CTL Model. This research was conducted using interactive qualitative methods and Classroom Action Research (CAR) which was conducted in 2 cycles. Each cycle included planning, implementation, observation, and reflection. The subjects of this research were the students of class VIII.1 odd semester SMP Negeri 2 Lubuk Pakam Kab. Deli Serdang. While the object is Contextual Teaching and Learning Model. Based on the data analysis, it can be concluded that in cycle 1 the students' learning completeness in this material was only 69.29, while in cycle 2 it was applied the Contextual Teaching and Learning Model. Learning (CTL) increased in cycle 2 the average value increased to 87.14. Student response also increased, data from observations of student activity from 62.50% in cycle 1, increased in cycle 2 to 85.42%.